DEFENDING THE EMPIRE: ANALYZING MILITARY RECRUITMENT IN COLONIAL MIANWALI DISTRICT - Sumbal, Saadia (European Scientific Journal, ESJ, 2014)
This paper brings into focus the military traditions in Mianwali District in Colonial era. Due to its proximity to Salt Range areas of Jhelum, chakwal, and Shahpur districts, the recruits in this region were considered ideally suited for the harsh military conditions, primarily owing to their physique. An increasingly large number of recruits served in the colonial army in order to supplement their agricultural income derived from haphazard cultivation. Mianwali is a region inhabited by various tribes, kinship or biradaries as it is put in local parlance. The district had overwhelmingly Pathan population along with other communities including Jats, Baluch, Rajputs and Khattaks. Tribes and castes not only symbolized strength and power but also served as the identity marker. Ethnic prejudices and sense of superiority of one clan over another were the defining features among Pathan clans. Economic interests and ethnic prejudices had fostered inter-tribal rivalries and stunted mutual harmony and social cohesion. Tribes lie at the heart of rural identity. Tribal identity itself served as a wedge, precluding unity among the tribes. The British recognized the social and political importance of this tribal structure to strengthen colonial rule in this region. Colonial interests were served by the policy of cooption of rural elite, who served as intermediaries in the colonial hierarchy of power. A class of landowners was created in the district to serve as a nexus between state and people by means of lucrative grants. Hence a tribally based local administration was conjured up. The rural leaders legitimized their authority through their lands, an insignia of power and prestige and their connection with the British officials. The local leaders emerged from the Khawanins of Isa Khel, Nawabs of Kalabagh, landed aristocrats of Piplan,Wan Bhachran, Bhakkar, Where as other tribes faced economic marginalization. This gap subsequently exacerbated the inter-tribal misgivings. The colonial state and rural elite developed a nexus to relegate the district to economic marginalization, as a result enlistment in army was left as the only alternative for subsistence.